Human metapneumovirus M2-2 protein inhibits RIG-I signaling by preventing TRIM25-mediated RIG-I ubiquitination - Tanaka, Yukie; Morita, Naoko; Kitagawa, Yoshinori; Gotoh, Bin; Komatsu, Takayuki (Frontiers in Immunology, 2022)
Retinoic acid-inducible gene I (RIG-I) is a receptor that senses viral RNA and interacts with mitochondrial antiviral signaling (MAVS) protein, leading to the production of type I interferons and inflammatory cytokines to establish an antiviral state. This signaling axis is initiated by K63-linked RIG-I ubiquitination, mediated by the E3 ubiquitin ligase TRIM25. However, many viruses, including several members of the family Paramyxoviridae and human respiratory syncytial virus (HRSV), a member of the family Pneumoviridae, escape the immune system by targeting RIG-I/TRIM25 signaling. In this study, we screened human metapneumovirus (HMPV) open reading frames (ORFs) for their ability to block RIG-I signaling reconstituted in HEK293T cells by transfection with TRIM25 and RIG-CARD (an N-terminal CARD domain that is constitutively active in RIG-I signaling). HMPV M2-2 was the most potent inhibitor of RIG-I/TRIM25-mediated interferon (IFN)-β activation. M2-2 silencing induced the activation of transcription factors (IRF and NF-kB) downstream of RIG-I signaling in A549 cells. Moreover, M2-2 inhibited RIG-I ubiquitination and CARD-dependent interactions with MAVS. Immunoprecipitation revealed that M2-2 forms a stable complex with RIG-I CARD/TRIM25 via direct interaction with the SPRY domain of TRIM25. Similarly, HRSV NS1 also formed a stable complex with RIG-I CARD/TRIM25 and inhibited RIG-I ubiquitination. Notably, the inhibitory actions of HMPV M2-2 and HRSV NS1 are similar to those of V proteins of several members of the Paramyxovirinae family. Therefore, in this study, we have identified a novel mechanism of immune escape by HMPV, similar to that of Pneumoviridae and Paramyxoviridae family members.